If you mean (x+a){x^2-(ax/x)}, then
= (x+a)(x^2-a)
= x^3 - ax + ax^2 - a^2
If you mean (x+a){(x^2-ax)/x}, then
= (x+a)(x-a)
= x^2 - a^2
Hope that's helpful.
Hello, kwtolley!
Please check the exact wording of the problem.
The way it's given, it's completely wrong!
"Factor"? . . . But it's already factored!Factor the polynomial:
"Polynomial"? . . . We have the product and quotient of three polynomials!
Other than that, the problem is fine . . . it should have said:
. . Simplify: .
Factor and reduce: .